2019
DOI: 10.4018/ijskd.2019070103
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Success of Windows Domain Network (WDN) Using the DeLone and McLean Information System (IS) Success Model

Abstract: This work attempts to evaluate the success of the Windows Domain Network (WDN) using the DeLone and McLean information system (IS) success model. With a case in a University in the Philippines, this study utilized a total of 290 valid responses from 424 participants. Results using structural equation modeling (SEM) indicate that information, service, and system quality demonstrate a moderately positive relationship with system usage and have a significant relationship with user satisfaction. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
2
18
1
Order By: Relevance
“…A further extension of TAM (i.e., e-TAM) is developed to explain software and IT product behavior perspective [23,34,35,67]. This model is recently implemented by [23] by proposing a consumer acceptance model for the Home Energy Management System (HEMS).…”
Section: Users' Acceptance Of a Technology Supporting Energy Efficienmentioning
confidence: 99%
See 4 more Smart Citations
“…A further extension of TAM (i.e., e-TAM) is developed to explain software and IT product behavior perspective [23,34,35,67]. This model is recently implemented by [23] by proposing a consumer acceptance model for the Home Energy Management System (HEMS).…”
Section: Users' Acceptance Of a Technology Supporting Energy Efficienmentioning
confidence: 99%
“…These variables are independent of each other; hence, there is no mediating relationship between these variables. The consumer acceptance model for HEMS previously developed by [23] has been recently referred to by [35] with a few changes. Here, they found that economic benefit, social contribution, and environmental responsibility has a positive influence on the usefulness of HEMS.…”
Section: Users' Acceptance Of a Technology Supporting Energy Efficienmentioning
confidence: 99%
See 3 more Smart Citations